A multi-channel optical fibre-based smartphone spectrophotometer for measuring the spectra of LED colours. (18th May 2021) - Puttharugsa, Chokchai; Srikhirin, Toemsak; Pipatpanukul, Chinnawut; Houngkamhang, Nongluck
Abstract: This paper demonstrates the use of a smartphone as a low-cost multi-channel optical fibre spectrophotometer suitable for physics laboratory classes. A custom-designed cradle and structure support were fabricated using 3D printing. The plastic optical fibres were arranged and inserted into the hole of the cradle to guide the light to the rear camera of the smartphone. Here, we describe the multi-channel optical fibre-based smartphone spectrophotometer for measuring the spectra of different LED colours.